Students’ Perceptions of Online Learning During the COVID-19 Pandemic: A Study of Undergraduate Students from an International University, Thailand - Thanavisuth, Chayada (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The outbreak of COVID-19 had an impact on educational systems worldwide. This study was aimed at investigating the perceptions of students towards online learning during the COVID-19 pandemic. Two hundred fifty-five undergraduate students from a private international university in Thailand participated in this study. Data were collected using the adapted version of Students’ Perception Questionnaire (SPQ) items from Bączek et al. through an Google Forms online survey. The research objective was examined by basic descriptive statistics (percentage, means and standard deviations). Results showed that student participants prefer both online and onsite learning. The most strongest advantage of online learning is allowing participants to stay at home (72.15%) whereas the participants chose technical problems (73.33%) and lack of interactions with friends (71.37%) as the major disadvantages. The participants perceived that online learning was effective that helped increase knowledge (35.29%), active classroom activities (33.33%) and enjoyable (30.2%). Based on the research findings, suggestions and recommendations to improve the higher education online learning in the future and pedagogical implications are provided. Keywords: COVID-19, online learning, students’ perceptions, undergraduate students, Thai private international university